Evaluating early interim fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography with the SUVmax-liver-based interpretation for predicting the outcome in diffuse large B-cell lymphoma. Issue 9 (2nd September 2017) - Fan, Yang; Zhang, Yuewei; Yang, Zhi; Ying, Zhitao; Zhou, Nina; Liu, Chen; Song, Yuqin; Zhu, Jun; Wang, Xuejuan
Abstract: Interim 18 F-FDG PET/CT is an effective predictor in patients with DLBCL, but the standard evaluating criteria were controversial. In this study, investigators tried to investigate whether the liver SUVmax (SUVmax-liver )-based interpretation could improve the accuracy of predicting the outcomes, comparing with the Deauville five-point scale (5-PS) and the reduction rate of the maximum standardized uptake value (ΔSUVmax ) criteria. In 119 patients, PET/CT after two chemotherapy cycles (PET2) were evaluated with the SUVmax-liver -based interpretation, 5-PS, and ΔSUVmax criteria. Uni- and multivariate analyses were performed. The optimal threshold for the SUVmax-liver -based interpretation was 1.6 fold of SUVmax-liver . Using the SUVmax-liver -based interpretation, the 3-year PFS and OS were 19.9% and 33.0% for patients with a positive residue while 78.2% and 86.4% for patients with negative results ( p  < .001). SUVmax-liver -based interpretation demonstrated slightly superior accuracy, and was independent predictor for PFS and OS ( p  ≤ .001). Thus, early interim 18 F-FDG PET/CT effectively predicts the outcome in patients with DLBCL using SUVmax-liver -based interpretation.